Pengaruh Investasi dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi Di Kawasan Timur dan Barat Indonesia - Suparta, I Wayan; Alfajar, Ridho (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Economic growth disparities between Western and Eastern Indonesia remain a major challenge in achieving equitable national development. Based on data from the Statistics Indonesia (BPS, 2024), Indonesia’s economic growth increased from –2.07 percent in 2020 to 3.69 percent in 2021, 5.31 percent in 2022, and remained stable at around 5.05 percent in 2023. Although this reflects a solid economic recovery, regional inequality remains evident. Western Indonesia, which includes Sumatra, Java, and parts of Kalimantan, contributes approximately 80 percent to the national Gross Domestic Product (GDP), while Eastern Indonesia—comprising Sulawesi, Bali–Nusa Tenggara, Maluku, and Papua—accounts for only about 20 percent. This imbalance illustrates differences in investment distribution and labor capacity between the two regions. The study aims to analyze the influence of investment and labor on economic growth in both the western and eastern regions during the 2020–2024 period. The research employs a quantitative approach using annual panel data from all provinces in both regions, and applies the Fixed Effect Model (FEM) with robust standard errors to address potential violations of classical assumptions. The results indicate that in the western region, both investment and labor have a positive and significant effect on economic growth. In contrast, in the eastern region, only labor shows a significant influence, while investment does not have a statistically significant impact.